Surveillance data in CDI - Curran, Margaret; Herceg, Ana (Communicable Diseases Intelligence, 1997)
The Communicable Diseases Surveillance section of Communicable Diseases Intelligence (CDI) includes reports from a number of national surveillance schemes. These schemes are conducted to monitor the occur rence of communicable diseases in Australia, to detect trends, to highlight needs for further investigation and to implement or manage control measures. This article describes the surveillance schemes which are routinely reported on in CDI.